(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper seeks to compare the GST and VAT Systems. Goods and Services Tax (GST) and Value-Added Tax (VAT) systems reveals key differences and similarities in their implementation, administration, and impact. Both GST and VAT are indirect taxes applied to the consumption of goods and services, designed to tax the value added at each stage of production and distribution. VAT, established in various forms worldwide, involves taxing goods and services at multiple stages of the supply chain with businesses claiming credits for tax paid on inputs. VAT systems often feature varying rates, including standard, reduced, and exempt categories, reflecting diverse economic and policy considerations. The complexity of VAT can arise from its multi-stage nature and the administrative burden placed on businesses to track and report VAT across transactions. GST, introduced to simplify and unify indirect tax regimes, merges VAT with other taxes like excise and service tax into a single system. GST is typically applied to both goods and services with a consistent tax rate structure, including multiple tiers to address different needs. The system aims to reduce tax cascading by allowing input tax credits and streamline compliance through a unified framework. However, the effectiveness of GST depends on its design, the clarity of regulations, and the efficiency of the technological infrastructure supporting tax administration. This comparative analysis highlights that while VAT and GST share common goals of reducing tax cascading and enhancing efficiency, GST often provides a more streamlined approach by integrating various taxes into a single system. The choice between VAT and GST depends on a country’s specific administrative, economic, and policy objectives, each having unique implications for tax compliance and economic impact.